Geochemistry of Cayambe-Coca (core C3) peat core from Ecuador - Hribjlan, John (PANGAEA, 2021)
Geochemistry data of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.
Keywords: C-PEAT; Peatland